An edition with introduction and commentary of John Blount's English translation of Nicholas Upton's De studio militari - Walker, CG (1998)
This thesis presents an edition, with introduction and commentary, of John Blount’s early sixteenth century English translation of Nicholas Upton’s De Studio Militari, a highly influential chivalric text written in 1446. It was comprised of four books, the first two provide a legal justification and discussion of conflict, and the last two a discussion of the theory and practice of heraldry. The translation survives in one copy, which is held in the Bodleian Library (Bodl. MS Eng.misc.d.227). The thesis is presented in two volumes: the first is the introduction and commentary, the second the text itself. The introduction begins with a biography of Upton and Blount and places the production of both the original De Studio Militari and the translation in context. After the biographies, each of the four books is introduced each with a chapter to itself, with Book Four divided into two chapters; one examining Upton’s discussion of beasts and the other examining Upton’s discussion of inanimate charges. These chapters outline sources used by Upton for the information he presented and compare the discourse Upton made with contemporary literature and an evaluation of De Studio Militari in its historical context. This ends volume one of the thesis. The second volume opens with a discussion of the families of De Studio Militari manuscripts and the position of John Blount’s translation in relation to these, and the individual characteristics of Blount’s translation. After this I outline the editorial conventions that I have used in the presentation of the manuscript: this is followed by the description of the manuscript of the English translation of De Studio Militari. After this is a list of all identified surviving manuscripts of De Studio Militari. There follows the text of the translation itself, transcribed word for word from the manuscript. I have inserted illustrations and modern punctuation into the transcript, and have added references that were omitted from the translation, which appear in the Latin versions of the text. Upton’s introduction to De Studio Militari which is not in the translation, a section missed by Blount from chapter eighteen of Book One, and a list of the authorities which Upton cited are included as appendices.